The nutrition education group and its effectiveness in obese patients treating - Moreira, Priscila (2013)
Introduction: Obesity is now viewed as an independent risk factor for coronary events, since even after controlling for associated diseases, such as hypertension, dyslipidemia and diabetes mellitus, the risk remains high. Objective: To evaluate the anthropometric and nutritional, noting the reduction in weight and waist circumference and change in dietary pattern of patients treated by the protocol of nutritional group. Materials and Methods: We conducted nutritional counseling group with hypocaloric diet and slimming and meetings addressing healthy lifestyles, with 40 obese patients (BMI ≥ 30 kg / m²), of both sexes, biweekly for 6 months. We evaluated the changes in weight, waist circumference and dietary habits that. Results: After the monitoring period, we observed an average weight reduction of 5.9% and waist circumference by 5.2% (p = 0.000). An improvement in eating patterns, both with respect to the total caloric value, which showed an average reduction of 27% (p = 0.000), from baseline to the end of the program, with respect to consumption of macro and micronutrients, which was a reduction of 55.66% in the consumption of sodium (p = 0.000) and 46.45% increase in fiber intake (p = 0.000). Conclusion: The program proved to be very effective for reducing weight and eating habits. Shares of Nutrition Education Group should be encouraged and enhanced, helping to combat obesity and its comorbidities.